Implementation of Music Learning for Autistic Students in Grade VI at a Special School (SLB) - Muhammad Budi Zakia Sani; Muhammad Iqbal; Rahmat Rahmat; Vivi Ervina Dewi (Borneo Research and Education Center, 2026)
This study aims to describe the implementation of music learning for students with Autism Spectrum Disorder (ASD) at SLB-C Negeri Pembina South Kalimantan. Using a descriptive qualitative method, the participants of this study consisted of three autistic students in the sixth grade. Data were collected through observation, interviews with the teacher, and documentation. The data analysis process included data reduction, thematic data display, and conclusion drawing. The results indicate that music learning was implemented by modifying a combination of question-and-answer and direct practice methods using the pianica instrument. This learning approach indicated positive support for student learning engagement, as evidenced by increased focus in the classroom, the ability to remember instructions on how to use musical instruments (cognitive), and improved motor coordination between the fingers, eyes, and mouth. In conclusion, music learning practices can serve as an adaptive alternative approach to support the learning process of autistic students.